2018
DOI: 10.1111/hepr.13072
|View full text |Cite
|
Sign up to set email alerts
|

Maternal viral load and hepatitis B virus mother‐to‐child transmission risk: A systematic review and meta‐analysis

Abstract: Our meta-analysis indicated that maternal viral load was an important risk factor for MTCT in HBeAg-positive mothers, and maternal viral load was dose-dependent with HBV MTCT incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
(88 reference statements)
2
23
0
Order By: Relevance
“…HBV vaccination starting at birth is approximately 95% effective (10). Aside from host factors that may interfere with vaccine response (host genetics, immune status, etc), virological factors, such as maternal HBV DNA levels (>7 log 10 IU/mL; (11)) and HBeAg positivity, can have a significant impact on the risk of chronic infection in infants born to chronically infected mothers. Although reports have suggested the prevalence of HBsAg mutants are increasing, which may compromise the long-term success of vaccination programs (12), it has been repeatedly shown that mutations verified to result in immune escape, such as G145R, remain a rare exceptional cause of vaccine breakthrough, and that over time the HBsAg mutation frequency has not accelerated due to immunization (13).…”
Section: Discussionmentioning
confidence: 99%
“…HBV vaccination starting at birth is approximately 95% effective (10). Aside from host factors that may interfere with vaccine response (host genetics, immune status, etc), virological factors, such as maternal HBV DNA levels (>7 log 10 IU/mL; (11)) and HBeAg positivity, can have a significant impact on the risk of chronic infection in infants born to chronically infected mothers. Although reports have suggested the prevalence of HBsAg mutants are increasing, which may compromise the long-term success of vaccination programs (12), it has been repeatedly shown that mutations verified to result in immune escape, such as G145R, remain a rare exceptional cause of vaccine breakthrough, and that over time the HBsAg mutation frequency has not accelerated due to immunization (13).…”
Section: Discussionmentioning
confidence: 99%
“…According to a deterministic mathematical transmission modelling study, approximately 210 million infants had been protected from HBV infection, owing to the application of the HBVac, by the year 2015 . However, the MTCT is more likely to occur in pregnant women with high viral load (HBV DNA > 10 6 IU/mL) and no antiviral treatment, even if both HBIG and HBVac immunizations have been applied, namely, interruption failure . Nucleo(t)side analogues (NAs), the most widely used orally administered agents against HBV, are expected to reduce the chance of vertical transmission via inhibiting the replication of maternal HBV.…”
Section: Introductionmentioning
confidence: 99%
“…The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the included observational studies. NOS involves a total of eight items divided into three categories: selection (4), comparability (1) and exposure (3). The scale ranges from zero to nine points.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Chronic hepatitis B (CHB) remains a serious global public health issue [1][2][3][4][5] . According to data from the World Health Organization (WHO), an estimated 257 million people are infected with hepatitis B virus (HBV) 3 . Mother-to-child transmission (MTCT) is the major cause of CHB infection 3,6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation